The Development and Evaluation of A Mhealth, Community Education and Navigation Intervention to Improve Clinical Breast Examination Uptake in Segamat Malaysia: A Randomised Controlled Trial - De´sire´e Schlieman; Aminatul Saadiah Abdul Jamil; Devi Mohan; Min Min Tan; Christopher R. Cardwell; Roshidi Ismail; Nur Aishah Taib; Tin Tin Su; Michael Donnelly (Public Library of Science, 2024)
Indexed by Scopus/ERA